Connectivity of Discretionary Status in State Administrative Court Lawsuit: Implications After Law Number 6 of 2023 on Amendments to the Job Creation PERPPU - Risadde, Fahmi Rosya; Widiarto, Aan Eko; Qurbani, Indah Dwi (Pencerah, 2024)
This research aims to analyze the impact of regulatory changes on the handling of discretionary authority within the State Administrative Court (PTUN) in Indonesia. Specifically, it examines how the legal status of discretion as an object of dispute has evolved following the enactment of Law No. 6 of 2023, which amended the Job Creation Perppu. The study focuses on how this legislative reform affects the acceptance and settlement of lawsuits related to discretionary decisions by public officials, as well as the legal boundaries that define which discretionary actions can be challenged in court. Using a normative juridical approach and in particular, this research employs statutory analysis to evaluate relevant laws and regulations, case studies to analyze precedents in PTUN decisions, and a comparative approach to assess differences in discretionary oversight before and after the enactment of Law No. 6 of 2023. The findings show that Law No. 6 of 2023 enhances judicial oversight of discretionary actions by allowing challenges based on both procedural and substantive grounds. It sets clearer limits on discretionary authority, requiring decisions to meet standards of transparency, accountability, and public interest. This reform strengthens the PTUN's role in reviewing not only the legality but also the justification of administrative decisions, offering citizens greater protection against arbitrary discretion and promoting good governance. This research contributes to academic discourse on administrative law by offering specific insights into how Law No. 6 of 2023 impacts discretionary authority and PTUN supervision. It highlights that the law now requires discretionary acts to meet stricter standards, focusing on procedural transparency and substantive justification. For instance, public officials must ensure their decisions align with good governance principles, and PTUN now plays a stronger role in assessing the substance of these actions. This provides legal practitioners with clearer guidelines for handling disputes involving discretion, particularly regarding the balance between decision-making flexibility and citizen protection.